2020
DOI: 10.1029/2019jf005428
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Bluff Evolution in Response to a Rapid Rise in Surface Water Level

Abstract: The water level in Lake Michigan began rising in 2013. Historically, erosion of the bluffs along the shoreline increases when water levels rise and remain high, beginning at the toe and propagating upslope, potentially damaging infrastructure near the crest. Bluff retreat is well understood over decadal scales; however, transient perturbations of force instabilities from toe to crest during disequilibrium are difficult to document. This instability for three bluffs, distinguished by height, was investigated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…While it is known that water levels in the Great Lakes vary over 20-30 year cycles (Gronewold & Rood, 2019), recent future projections estimate that by 2040-2049 average annual water levels of Lake Superior, Lake Michigan-Huron and Lake Erie are projected to increase by +0.19, +0.44, +0.28 m, respectively due to an increase in over-lake precipitation and basin runoff compared to relatively smaller increase in lake evaporation (Kayastha et al, 2022). While there are no studies predicting future erosion rates and shoreline recession in response to the projected water level changes for the Great Lakes, several studies show that high water levels correspond with accelerated shoreline erosion, including bluff erosion, on short time scales (e.g., Kaczmarek et al, 2016;Krueger et al, 2020). For instance, Castedo et al (2013) simulated erosion rates to range between 0.5 and 1.5 m/yr in response to lake water level variations of 0.5-1 m. A more recent study by Volpano et al (2020) on coastal bluff erosion along Western Lake Michigan's shoreline found that erosion rates increased from 0.18 to 0.43 m/yr between 2009 and 2014 (period with below long term average water levels) to 0.49-1.19 m/yr between 2014 and 2018 (period with above long-term average water levels).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is known that water levels in the Great Lakes vary over 20-30 year cycles (Gronewold & Rood, 2019), recent future projections estimate that by 2040-2049 average annual water levels of Lake Superior, Lake Michigan-Huron and Lake Erie are projected to increase by +0.19, +0.44, +0.28 m, respectively due to an increase in over-lake precipitation and basin runoff compared to relatively smaller increase in lake evaporation (Kayastha et al, 2022). While there are no studies predicting future erosion rates and shoreline recession in response to the projected water level changes for the Great Lakes, several studies show that high water levels correspond with accelerated shoreline erosion, including bluff erosion, on short time scales (e.g., Kaczmarek et al, 2016;Krueger et al, 2020). For instance, Castedo et al (2013) simulated erosion rates to range between 0.5 and 1.5 m/yr in response to lake water level variations of 0.5-1 m. A more recent study by Volpano et al (2020) on coastal bluff erosion along Western Lake Michigan's shoreline found that erosion rates increased from 0.18 to 0.43 m/yr between 2009 and 2014 (period with below long term average water levels) to 0.49-1.19 m/yr between 2014 and 2018 (period with above long-term average water levels).…”
Section: Discussionmentioning
confidence: 99%
“…While it is known that water levels in the Great Lakes vary over 20–30 year cycles (Gronewold & Rood, 2019), recent future projections estimate that by 2040–2049 average annual water levels of Lake Superior, Lake Michigan‐Huron and Lake Erie are projected to increase by +0.19, +0.44, +0.28 m, respectively due to an increase in over‐lake precipitation and basin runoff compared to relatively smaller increase in lake evaporation (Kayastha et al., 2022). While there are no studies predicting future erosion rates and shoreline recession in response to the projected water level changes for the Great Lakes, several studies show that high water levels correspond with accelerated shoreline erosion, including bluff erosion, on short time scales (e.g., Kaczmarek et al., 2016; Krueger et al., 2020). For instance, Castedo et al.…”
Section: Discussionmentioning
confidence: 99%